2007
DOI: 10.1371/journal.pgen.0030207
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Inflammation/NF-κB Signaling in Infants Born to Arsenic-Exposed Mothers

Abstract: The long-term health outcome of prenatal exposure to arsenic has been associated with increased mortality in human populations. In this study, the extent to which maternal arsenic exposure impacts gene expression in the newborn was addressed. We monitored gene expression profiles in a population of newborns whose mothers experienced varying levels of arsenic exposure during pregnancy. Through the application of machine learning–based two-class prediction algorithms, we identified expression signatures from bab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
196
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(212 citation statements)
references
References 36 publications
11
196
0
Order By: Relevance
“…These observations suggest that any pro-inflammatory stimulus or agent that gains entry to the body through different routes could induce the same negative effect on human cognitive functions. In this sense, several reports have shown that acute or chronic exposure to iAs or its methylated metabolites lead to inflammatory responses activation in diverse cell types [15][16][17]; therefore, exposure to arsenicals may increase the risk for cognitive impairment through the induction of a sustained inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that any pro-inflammatory stimulus or agent that gains entry to the body through different routes could induce the same negative effect on human cognitive functions. In this sense, several reports have shown that acute or chronic exposure to iAs or its methylated metabolites lead to inflammatory responses activation in diverse cell types [15][16][17]; therefore, exposure to arsenicals may increase the risk for cognitive impairment through the induction of a sustained inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these loci exhibited dose-response linear relationships between methylation and arsenic exposure including genes encoding oestrogen receptor alpha and a nuclear receptor co-activator, which given the importance of hormonal signalling in fetal development may have health consequences. A study in Thailand [38] compared RNA transcripts in the cord blood of newborns born to mothers differentially exposed to arsenic using microarray analysis. They found that prenatal arsenic exposure had a strong impact on the transcriptome of the newborn, with a subset of 11 transcripts highly predictive of arsenic exposure.…”
Section: Internal Pregnancy Exposome Studiesmentioning
confidence: 99%
“…Rager et al [39•] performed a similar analysis in a Mexican birth cohort; however, they also measured levels of miRNAs, small non-coding RNAs involved in regulation of messenger RNA (mRNA) translation. They identified 12 References selected from PubMed search (see Table 1) and recent reviews [4,45,46] (including citing and cited references) to represent state of the science miRNAs associated with arsenic exposure, many of which were known to have roles in carcinogenesis, and 334 mRNA transcripts including 28 identified in the study of Fry et al [38]. They found that a third of miRNA-mRNA pairings, predicted computationally based on target sequences, were correlated in their analysis.…”
Section: Internal Pregnancy Exposome Studiesmentioning
confidence: 99%
“…Critical to understanding the importance of these exposures will be investigation of the associated cellular and physiologic effects to provide biological plausibility to the reported exposure-disease associations. A promising recent example in this regard comes from the work of Fry and colleagues (18), who showed that arsenic exposure in pregnant Thai women was related to differences in gene expression in the cord blood at the time of birth of their child. Among the affected biological pathways were those indicative of stress, inflammation, metal exposure, and apoptosis.…”
Section: Future Perspectivesmentioning
confidence: 99%